Características agronômicas, físico-químicas e sensoriais de linhagens de pimenta Biquinho cultivadas em sistema orgânico - Santos, Adriano Sebastião dos (2018)
The pipper “Biquinho” is more and more valued in the consumer market, being attractive mainly for the taste and for its use as canned, jam, sauces and dry spices. Despite the great demand of the market, there are few cultivars available for production in organic systems, where there are few information on the agronomic, physical-chemical and sensorial characteristics for these cultivars of interest to producers and consumers. The objective of this research was to evaluate the agronomic performance, physico-chemical and sensorial characteristics of a cultivar BRS Moema and two lineages 37701 and 313605 of pipper “Biquinho” (Capsicum chinense) cultivated in an organic production system. The color, pH, soluble solids, titratable acidity, phenolics and ascorbic acid were analyzed for the agronomic parameters, height, colony diameter, chlorophyll, numbers of floral buds, leaves, flowers and fruits and the possible differences and sensorial preference among the cultivars. The experimental design was in randomized blocks, consisting of three treatments and six blocks. It was verified that the best agronomic results 105 days after planting were obtained for cultivar BRS Moema (height, chlorophyll, diameter of the neck, leaves and fruits) and lineage 37701 (flower buds, chlorophyll and flowers). For the physico-chemical analyzes, the 37701 and 313605 strains obtained better results between pH, titratable acidity and phenolic compounds. For the cultivar BRS Moema, it presented a superior value for ascorbic acid and soluble solids. The instrumental color analysis showed that there was a difference between the parameter L, * a, * b, Croma and Hue among the samples. For the sensory analyzes there was difference for the attributes size, spicy aroma, crisp texture and preference between the samples, it was verified that the lines 37701 and 313605 have a higher preference, probably related to the spicy aroma attributes and the crunchy texture of the sample.